The great human diasporas the history of diversity and evolution - Cavalli-Sforza, Luigi L. 1922-2018; Cavalli-Sforza, Francesco (Helix books, 1995)
After providing a thorough grounding in evolutionary theory, Cavalli-Sforza takes readers back to the heady times of 1961-62 when he and a few colleagues were able to bring together genetic data on blood groups for fifteen populations spread out on five continents. By computing the genetic distance between pairs of populations, these scientists were able to develop an evolutionary tree that looks surprisingly like the ones reconstructed today, even with fifteen times more information. Using this crude tree, scientists could trace the approximate routes modern humans took in colonizing the earth 100,000 years ago and discover when populations split off from each other to form new groups